2005
DOI: 10.1111/j.1472-765x.2005.01689.x
|View full text |Cite
|
Sign up to set email alerts
|

Removal of micro-organisms in a small-scale hydroponics wastewater treatment system

Abstract: Aims: To measure the microbial removal capacity of a small-scale hydroponics wastewater treatment plant. Methods and Results: Paired samples were taken from untreated, partly-treated and treated wastewater and analysed for faecal microbial indicators, i.e. coliforms, Escherichia coli, enterococci, Clostridium perfringens spores and somatic coliphages, by culture based methods. Escherichia coli was never detected in effluent water after >5AE8-log removal. Enterococci, coliforms, spores and coliphages were remov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
1
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 26 publications
0
8
1
2
Order By: Relevance
“…The great majority of studies on hydroponics with reclaimed water are at laboratory scale. Small‐scale hydroponics wastewater treatment systems are capable of removing microorganisms satisfactorily, including virus and (oo)cyst process indicators, thus hydroponics can be an alternative to conventional wastewater treatment (Ottoson et al ., 2005). Ndulini et al .…”
Section: Hydroponic Systems With Wastewatermentioning
confidence: 99%
“…The great majority of studies on hydroponics with reclaimed water are at laboratory scale. Small‐scale hydroponics wastewater treatment systems are capable of removing microorganisms satisfactorily, including virus and (oo)cyst process indicators, thus hydroponics can be an alternative to conventional wastewater treatment (Ottoson et al ., 2005). Ndulini et al .…”
Section: Hydroponic Systems With Wastewatermentioning
confidence: 99%
“…Besides, hydroponic systems have been reported to enhance the removal efficiency of pathogens, in wastewater treatment system (Ndulini et al, 2018). These researchers showed a removal efficiency of 92.77% for faecal coliforms removal, using of Bidenspilosa L. and Amaranthushybridus L. In their study, Ottoson et al (2005) have also been shown that hydroponics can be an alternative to conventional wastewater treatment through the virus and (oo)cyst removal. On the other hand, hydroponic systems can help in biomass production for value-added crops thereby improving food security and income generation among poor communities (Eregno et al, 2017;Jesse et al, 2019).…”
Section: Introductionmentioning
confidence: 97%
“…Sendo assim, um sistema de tratamento representa um processo importante para a melhoria da qualidade da água residual, além de implementar cultivos mais sustentáveis. Diversos tipos de sistemas de tratamento podem ser utilizados e, dentre eles, o emprego das macrófitas aquáticas em alagados artificiais representa um sistema bastante estudado para aquicultura, apresentando eficiência na redução das concentrações de poluentes inorgânicos, metais pesados, substâncias tóxicas, além de microrganismos patogênicos e/ou indicadores, como os coliformes termotolerantes (por exemplo, Escherichia coli) (ALMEIDA & ALMEIDA, 2006;DINIZ et al, 2005;SANTOS & CAMARGO, 2015;OTTOSON et al, 2005;PINTO et al, 2009).…”
Section: Introductionunclassified